Controllable micrometer positioning design of piezoelectric actuators using a robust fuzzy eliminator. (December 2019) - Chen, Yung-Yue; Lin, Li-Kai; Hung, Min-Hao
Abstract: To enhance the consistency and micro positioning accuracy of piezoelectric actuators made based on the batch manufacture, in this paper, a robust fuzzy eliminator with abilities to learn the disturbed actuators' models and to mitigate hysteresis is proposed. This proposed robust fuzzy eliminator can convert the error dynamics between the actuator output position and the desired trajectory into a linear disturbed form, and it quickly converge positioning errors. The residual modelling uncertainties attributed to parameter uncertainties are eliminated with a robust compensator exhibiting positioning error fine-tuning capability. From practical tests, this proposed control law depicts the promising positioning performance in the presence of modelling uncertainties (10%, 20%, and 40% modelling uncertainties), and each controlled piezoelectric actuator has an μm positioning accuracy. Highlights: The batch manufacture problem of piezoelectric actuators with controllable micro positioning ability is solved. From practical tests, a satisfactory micrometer positioning performance is delivered via this proposed method with respect to different level of modelling uncertainties: 10%, 20% and 40%, respectively. This proposed method is very meaningful and useful in a great number of fabrication of piezoelectric actuators because system parameters are unnecessary to be measured in prior.